Sleep positions of couples at sleep onset: association with relationship quality and relationship duration - Schredl, Michael; Pramschiefer, Emilie; Simon, Phillip; Runge, Hannah Lea; Onneken, Gabriele (International journal of dream research, 2022)
Most couples spend their nights together in one bed. Although several studies investigated the effect of co-sleeping on the sleep of the individuals, research into the sleep behavior of couples is scarce. One study, for example, looked at the hypothesis that relationship quality is related to the intimacy of the couple’s position at sleep onset, however, did not find a significant relationship due to small samples size. The present study was carried out to address this topic. Overall, 128 participants living in a stable relationship completed the online survey. Whereas the association between the intimacy of the sleep-onset position and relationship quality was only marginally significant (small effect size), couples living together and sleeping in larger beds are more likely to choose less intimate sleeping positions. This change in behavior, sleeping with greater distance to the partner, might be mediated by living together and bed size. In summary, the findings of this study indicate that studying sleep behavior and sleep arrangement of couples might be fruitful for basic sleep research and for the field of sleep medicine.